2018
DOI: 10.3390/ma11122574
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Silver Nanoparticles Using a Gas Phase Nanocluster Device and Preliminary Biological Uses

Abstract: Nanoparticles can be used in a large variety of applications, including magnetic sensing, biological, superconductivity, tissue engineering, and other fields. In this study, we explore the fabrication of gas phase silver nanoparticles using a sputtering evaporation source. This setup composed of a dual magnetron cluster source holds several advantages over other techniques. The system has independent control over the cluster concentration and a wide range of cluster size and materials that can be used for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The growing activity in this field has also stimulated the development of methods for the production of NPs and clusters with precise control of size, shape, and composition. In this regard, gas aggregation sources, [10][11][12] which allow obtaining core/shell structured nanoparticles 6,10 easily, were recently modified to achieve also high production rates 13 as in the case of wet chemistry synthesis techniques. Nevertheless, these latter methods have limitations in terms of the simplicity of the process, typically involving several processing steps, surface contamination and size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The growing activity in this field has also stimulated the development of methods for the production of NPs and clusters with precise control of size, shape, and composition. In this regard, gas aggregation sources, [10][11][12] which allow obtaining core/shell structured nanoparticles 6,10 easily, were recently modified to achieve also high production rates 13 as in the case of wet chemistry synthesis techniques. Nevertheless, these latter methods have limitations in terms of the simplicity of the process, typically involving several processing steps, surface contamination and size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The nanostructures were grown using the gas phase aggregation method with a cluster beam system manufactured by SinoRaybo NanoTech of China, located in the Physics Department of Federico Santa María Technical University, Valparaíso, Chile. [ 16 ] The equipment configuration includes an aggregation chamber, whose walls are cooled down with liquid nitrogen. The metal vapor source is a sputter gun with variable power, cooled by recirculating water and supplied with a controlled argon gas flow.…”
Section: Methodsmentioning
confidence: 99%
“…Morphology of the cell culture on the films were different when compared against the control (cells cultured without film). However, it has been reported that morphology of C2C12 depends of the kind of surface over which it is cultured, for instance, fibroblastic shape on plastic, rounded on Matrigel [10], or even star-shaped when cultured on nanocoated surfaces [29]. The morphology of myoblasts, myocytes, and myotubes in scaffolds can vary substantially from those in monolayer culture [2,8,10].…”
Section: Proliferation Of Muscle Fiber-like Biomassmentioning
confidence: 99%